Atopic dermatitis - Galli, Elena; Cinicola, Bianca; Carello, Rossella; Caimmi, Silvia; Brindisi, Giulia; De Castro, Giovanna; Zicari , Anna Maria; Tosca, Maria Angela; Manti, Sara; Martelli, Alberto; Calvani, Mauro; Cravidi, Claudio; et al. (Acta Biomedica Atenei Parmensis, 2020)
Atopic dermatitis (AD) is a common inflammatory skin disease, clinically characterized by recurrent eczematous lesions and intense itching, leading to excoriations and susceptibility to cutaneous infections. Although it is considered a pediatric disorder, mainly starting in infancy, it is also very common in adults. Etiology of AD is complex and multifactorial: interaction between genetic susceptibility and environment, but also cutaneous barrier impairment, change in microbiome composition and innate and adaptive immune dysregulation are the main factors involved in the pathogenesis of the disease. Originally, the disorder was considered mediated by an imbalance towards a T-helper 2 response and excessive IgE production to allergens, but now it is recognized as a lifelong disposition with variable clinical expressivity, where dysfunctions of the epidermal barrier, immune system and microbiome play a central role. AD leads to a substantial psycho-social burden on patients and their relatives and increases the risk of other allergic and non allergic disorders. The real economic impact of AD is difficult to measure due to the broad spectrum of disease severity and the multiple direct and indirect costs, but the overall medical expenses seem to be very high and similar to those of other diseases such as diabetes. Currently, a multiple therapeutic approach is aimed only at improving the skin state, reducing itching and keeping a stable condition. New safety and curative treatments may be developed only after enhancing our understanding on the pathogenesis of AD and the heterogeneity of its clinical manifestations.